If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 7y = 52 Solving x + 7y = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. x + 7y + -7y = 52 + -7y Combine like terms: 7y + -7y = 0 x + 0 = 52 + -7y x = 52 + -7y Simplifying x = 52 + -7y
| 1-3(2.x-1)=6 | | 3x-5(x-4)=-6+4x+14 | | 9=y/335 | | M^2+5m-3= | | 3+.03(115)= | | 4x=8y+1 | | 2(X+4)=3x-11 | | m=5-2sinx | | (13×3)-3)/3 | | 9/24/=12/n | | 0.5x-0.5=x+1.5 | | -75+7.5t=150 | | 2y(dx)+3x(dy)=0 | | 240=3v+f | | 7x^4=1 | | 5(y+2)=(2y+2) | | 3.15(x)+y=45 | | 3/4k-10=3 | | (8x^3+8x^2-40x+24)(4x^3+20x^2+12x-36)= | | y=1/4(8)-7 | | 1/2÷9 | | 3(5)+5(3)= | | x=8^(3/7) | | A-21=19 | | 3/y=y | | -1-2y=1 | | 2x-5(x-3)=-6+5x-43 | | 0.13x+x=25 | | 8(2h+5)=2(3x+5) | | 6a^3-14a^2+4a=2a | | 8/x=1 | | 0.05x+x=25 |